PENGUATAN KEPEMIMPINAN AKADEMIK DOSEN PERGURUAN TINGGI ISLAM MELALUI PENDAMPINGAN RISET DAN PENGABDIAN BERBASIS KEUNGGULAN INSTITUSI - Mawardi; Mona Novita; Elza Eka Putri; Oktawini Ofiani; Laili Asmani; Nur Husni (LPPM STAI Muhammadiyah Probolinggo, 2023)
Strengthening lecturers' academic leadership is a crucial aspect in improving the quality of the Tri Dharma of Higher Education, particularly in developing a culture of research and community service at Islamic universities. However, challenges remain in research management, proposal development, and the integration of institutional excellence into lecturers' academic agendas. This community service activity aims to strengthen academic leadership through mentoring research and community service based on institutional excellence, using a Community-Based Participatory Research (CBPR) approach. The target group is lecturers at INISMA Jambi, who are actively involved through research clinics and Community Service Programs (PKM), proposal development mentoring, and collaborative reflection and evaluation. The results of the activity indicate increased academic leadership capacity, the formation of a community of practice that supports a collaborative research culture, and an improved quality of research and community service proposals that are more systematic and relevant to institutional needs. The participatory approach enables the integration of Islamic leadership values ​​such as amanah (trustworthiness) and musyawarah (deliberation) into academic practice. This mentoring model has the potential to become a good practice in strengthening academic leadership and developing a sustainable research culture at Islamic universities.